Multiproduct Multinationals and the Quality of Innovation - Bakhtiari Sasan; Antonio Minniti; Alireza Naghavi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This research sheds light on the role of product scope on the innovation activity of multinational multi-product firms. We use patent citation data to break down innovation into two types by measuring the degree to which innovation performed by firms is fundamental and the extent to which the output of the R&D can be spread across different product lines. We focus on two features in multinational production: (i) fundamental innovation is geographically more difficult to transfer abroad to foreign production sites, (ii) learning spillovers can occur from international operations. The results reveal that the second effect is more likely to dominate when a firm is active in more product lines. We argue that a more diversified portfolio of products increases a firm's scope of learning from international operations, thereby enhancing its ability to engage in more fundamental research. In contrast, firms with less product lines that geographically separate production from innovation shift the innovation activities towards more specialized types of innovation.
Keywords: F12; F23; O31; O32; 330